Electrical сharacteristics study of heterojunction solar сells CdS/CIGS - Amar, H.; Amir, M.; Ghodbane, H.; Babes, B.; Kateb, M.N.; Zidane, M.A.; Rauane, A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2021)
In this work, we carried out the study of electrical characteristics with two-dimensional numerical analysis by using the Aided Design (TCAD Silvaco) software for CdS/CuInGaSe₂ (CIGS) thin solar cells. Their structure is composed of a thin CIGS solar cell in the configuration: ZnO(200 nm)/CdS(50 nm)/CIGS (350 nm)/Mo. Then ZnO is used for a conductive oxide contacted transparent front of the cell. For rear contact, the molybdenum (Mo) is used. The layer of the CdS window and the shape of the CIGS absorber form an n-p semiconductor heterojunction. The performance of the cell was evaluated by applying the defects created in the grain joints of polycrystalline CdS and CIGS material and the CIGS/CdS interface in the model, and the physical parameters used in the TCAD simulations have been calibrated to reproduce experimental data. The J–V characteristics are simulated under AM1.5 illumination conditions. The conversion efficiency (η) 20.10% has been reached, and the other characteristic parameters have been simulated: the open-circuit voltage (Vₒc) is 0.68 V, the circuit-current density (Jₛc) is equal to 36.91 mA/cm², and the form factor (FF) is 0.80. The simulation results showed that the molar fraction of the CIGS layer has an optimal value around 0.31 corresponding to a gap energy of 1.16 eV; this result is in very good agreement with that found experimentally. У роботі проведено дослідження електричних характеристик двовимірним чисельним аналізом за допомогою програмного забезпечення Aided Design (TCAD Silvaco) для тонких сонячних елементів CdS/CuInGaSe₂ (CIGS). Структура складається з тонкого сонячного елемента CIGS у конфігурації: ZnO (200 нм)/CdS (50 нм)/CIGS (350 нм)/Mo. Потім ZnO використано для провідного оксиду у контакті з прозорою передньою частиною елемента. Для зворотного контакту використовується молібден (Mo). Шар вікна CdS і форма поглинача CIGS – це напівпровідниковий n–p гетероперехід. Продуктивність елемента оцінювалася з урахуванням кількості дефектів, утворених поблизу стиків полікристалічного матеріалу CdS і CIGS біля інтерфейсу CdS/CIGS у моделі, а фізичні параметри для TCAD-моделювання були відкалібровані з метою відтворення експериментальних даних. J–V характеристики моделюються за умови освітлення AM1.5. Ефективність перетворення (η) досягає 20,10%. Також моделюються інші характерні параметри: напруга розімкнутого контуру (Vₒc) дорівнює 0,68 В, густина струму контуру (Jₛc) дорівнює 36,91 мА/см², та формфактор (FF) становить 0,80. Результати моделювання показали, що молярна частка х шару CIGS має оптимальне значення, близьке до 0,31, що відповідає енергії забороненої зони 1,16 еВ. Це дуже добре узгоджується з експериментальними значеннями.